Eksplorasi Penerapan Aplikasi Kahoot untuk Meningkatkan Motivasi Belajar Bahasa Arab Siswa Kelas 9 N MTsN 3 Jombang: Studi tentang Dampak Alat Pembelajaran Interaktif dalam Pendidikan Bahasa Arab - M. Awfi Zaki Zamani; Pipit Ertika Daristin; Rohmatun Inayah (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2024)
This study aims to explore the impact of using the Kahoot application to enhance Arabic language learning motivation among ninth-grade students of class IX N at MTsN 3 Jombang. A qualitative approach was employed, involving 30 students as participants. Data were collected through interviews, classroom observations, and questionnaires to gain an in-depth understanding of how Kahoot influences students' motivation. The results indicated that Kahoot significantly increased student engagement and made the learning process more interactive and enjoyable. Most students reported higher enthusiasm and active participation during lessons. These findings align with Self-Determination Theory, which emphasizes the importance of autonomy, competence, and social relatedness in fostering intrinsic motivation. Based on these results, it is recommended that educators incorporate Kahoot regularly into their teaching practices to improve student motivation and engagement in Arabic language learning